Endogenous glucocorticoids participate in retinal degeneration during continuous illumination - López, Ester María (2008)
Continuous illumination (CI) induces an oxidative stress of the retina which is involved in light-induced retinal degeneration (LIRD). As the increase of glucocorticoids (GC) could also collaborate in the damage, adrenalectomized (ADX) and sham-operated rats (control, CTL) were submitted to CI, and their eyes were studied at light and electron microscopic levels. After CI, ADX retinas were significantly thicker than CTL retinas. Retinal alterations appeared earlier and were severer in CTL than in ADX retinas. Corticosterone levels increased gradually in the sera of CTL rats along CI. These results suggest that adrenalectomy attenuates LIRD, supporting the hypothesis.